STRUCTURAL, MICROSTRUCTURAL AND DIELECTRIC PROPERTIES OF TRI-LAYERED AURIVILLIUS-TYPE STRUCTURE Bi4Ti3O12 FERROELECTRIC CERAMICS - Reis, I. C. [UNESP]; Silva, A. C. [UNESP]; Guo, R.; Bhalla, A. S.; Guerra, J. D. S.; Mahmoud, M. M.; Bhalla, A.; Bansal, N. P.; Singh, J. P.; Castro, RHR; Manjooran, N. J.; Pickrell, G.; et al. (Wiley-Blackwell, 2015)
In this work, the physical properties of rare-earth modified Bi4Ti3O12 (BT) system have been investigated. High-density ceramic samples were obtained from the solid-state reaction method. The structural and microstructural properties were studied from the x-ray and scanning electron microscopy techniques, respectively. The dielectric response has been analyzed in a wide temperature and frequency range and the influence of rare-earth concentration on the studied properties has been taken into account.